RANCANG BANGUN TONGKAT TUNANETRA DENGAN DETEKSI LUBANG DAN GENANGAN AIR BERBASIS ARDUINO - Bayu Prakoso (JIMSTEK: Jurnal Ilmiah Sains dan Teknologi, 2021)
Blind people are individuals who have visual impairments. Blindness can be classified into two groups, namely: total blindness (blind) and low vision. According to the indonesian Ministry of Health, the number of blind people in Indonesia is 1.5%. If Indonesia’s current population is 2.5 mmillion, there are at least 3.750.000 blind people, both in the blind and visually impaired category. Blind people have limitations in the sense of sight so that the mobility of the blind can use the stick. Conventional sticks are generally straight, long,, foldable, and in the form of the hollow aluminum tube with and outer radius of 6 mm and a density of 103 kg 2.7 ‘md. Blind conventional sticks still have many shortcomings, so that the development of technology in the form sensors makes it possible to make blind sticks with Arduino-based hole and puddle detection. This study aims to design and implement a blind sticks to detect holes and puddles-based Arduino. The data collection method used literature study, tool design and making as well as tool testing. The results show that when the stick moved forward, the sonsor succeeded in detecting a hole with a depth of 90cm – 140cm, and the sensor was also successful in detection and warning of the puddle with a depth of more then 1cm.